Pendampingan Pengembangan Usaha Bagi Pelaku Usaha Mikro Kecil dan Menengah “Baso Aci Cingcay Radja Rasa” di Kecamatan Rancaekek - Dadan Hamdani (LPPM Universitas Koperasi Indonesia, 2023)
Managers of Micro, Small, and Medium Enterprises (MSMEs) are one of the parties that play a role in advancing the community's economy, but there are still some deficiencies or they do not understand business management. Therefore, community service through the implementation of business development and assistance for business actors